Nuclear protein in testis midline carcinoma presenting in an infant as a pericardial mass with staging by 18F-fluorodeoxyglucose-positron emission tomography/computed tomography - Perkins, Crystal; Pucar, Darko; McDonough, Colleen; Williams, Hadyn (World Journal of Nuclear Medicine, 2017)
Nuclear protein in testis (NUT) midline carcinoma (NMC) is a rare, aggressive, lethal, epithelioid, poorly differentiated cancerfirst described in Japan in 1991, unique in that is defined genetically rather than by histological tissue of origin. It usually arises in the body midline and presents as a mass with metastasis. An infant presenting with pneumonia was found to have a pericardial mass, NMC resected, and subsequent staging positron emission tomography (PET) showing residual mediastinal tumor and midline abdominal metastases. Fewer than 100 cases of NMC have been reported in the literature, and PET appears to be the imaging modality of choice in complete staging and evaluation of treatment response.
Keywords: 18F-fluorodeoxyglucose-positron emission tomography/computed tomography; nuclear protein in testis midline carcinoma; squamous cell